2014
DOI: 10.14814/phy2.12066
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid effects in the late gestation ovine fetal lung

Abstract: This study was designed to determine the effects of corticosteroids at MR in the late‐gestation fetal lung. Since both the mineralocorticoid receptor (MR) and the glucocorticoid receptor (GR) are expressed at relatively high levels in the fetal lung, endogenous corticosteroids may act at MR as well as GR in the preterm fetal lung. The GR agonist, betamethasone, the MR agonist, aldosterone, or both were infused intravenously for 48 h in ovine fetuses of approximately 130 days gestation. Effects on airway pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…It is not known what effects mineralocorticoids have in the fetus. They may have roles alongside glucocorticoids in lung development 38 and the programming of future hypertension 39 in animal models. It has been postulated that progesterone metabolism through corticosterone to mineralocorticoids is involved in programming autism 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It is not known what effects mineralocorticoids have in the fetus. They may have roles alongside glucocorticoids in lung development 38 and the programming of future hypertension 39 in animal models. It has been postulated that progesterone metabolism through corticosterone to mineralocorticoids is involved in programming autism 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Without the onset of labour, the initiation of this surfactant secretion does not occur, meaning that the overall concentration does not reach the necessary levels needed for rapid transition at birth [ 11 ]. ECS deliveries before the prepartum increase of hormones also results in a reduction in the expression of additional proteins such as antioxidants and does not occur at its peak and necessary level [ 30 ]. This was highlighted in our study, as we showed an almost four fold reduction to the relative abundance of CYP1A1 .…”
Section: Discussionmentioning
confidence: 99%
“…The induction of SGK1 increases distal lung fluid absorption by activating α subnet of epithelial Na + channel (α-ENaC) [ 82 ] through Nedd4-2 suppression in fetal lung tissue [ 83 ]. By the same token, SGK1 in placental trophoblast contributes to normal sodium homeostasis in the bidirectional process of maternal–fetal fluid exchange by modulating trophoblast Na + transport under the stimulation of corticosteroids [ 84 ]. Besides, two single-nucleotide polymorphisms (SNPs) of SGK1 (rs1057293 and rs1743966) were reported to be related to transient tachypnea of the newborn (TTN) [ 85 ], proposing a protecting role in fetal growth and development [ 86 ].…”
Section: Sgk1 Involvement In Fetal Developmentmentioning
confidence: 99%